Giardia duodenalis: protein substrates degradation by trophozoite proteases - Coradi, S. T.; Guimaraes, S. (Springer, 2006)
The present investigation was undertaken to identify and characterize trophozoite proteases of five axenic strains of Giardia duodenalis isolated in Brazil and the reference strain Portland 1 isolated in the United States. Trophozoite cell lysates of each strain were analysed for the pattern of proteins and for proteolytic activity. Samples were tested in SDS-polyacrylamide gel electrophoresis for the protein profiles, and the detection of proteases in cell lysates was performed using substrate gel electrophoresis [gelatin, collagen, bovine serum albumin (BSA) and haemoglobin] and azocasein assays. Indeed, synthetic inhibitors were included in the assays to characterize the protease classes. Differences on the hydrolysis patterns of protein substrates were observed in relation to the substrate composition as much as the Giardia trophozoite strain. The substrate-containing gels revealed hydrolysis bands with molecular masses ranging from > 97 to 20-15 kDa, and most zones were common to the five strains. However, some pronounced differences could be detected in the BTU-11 pattern. Azocasein was also degraded; however, depending on the lysate assayed, the degree of substrate degradation was variable. It was observed that inhibitory effects are substrate-dependent since the activity was predominantly due to cysteine proteases against gelatin, collagen, BSA and azocasein substrates and due to serine against haemoglobin. The presence of aspartic protease and aminopeptidase activity in the lysates was also indicated.